Analysis of Workers' Understanding About Emergency Preparedness and Response To Disaster at The War Ship Division PT. PAL Indonesia - Marta Bela Kartika; Moch Sahri; Achmad Syafiuddin; Mursyidul Ibad (Jurnal KESANS : Kesehatan dan Sains, 2022)
Introduction: Indonesia has conditions where it is possible for disasters to occur caused by natural factors, non-natural factors and human factors. Increased understanding of emergency preparedness and response in the community, especially workers, needs to be done to reduce losses due to future disasters. Objective: The purpose of the study was to identify the level of understanding of workers about emergency preparedness and response in an effort to deal with disaster risk in the Warship Division of PT. Indonesian PAL. Method: This research uses quantitative method with descriptive research type. Result and Discussion: The results of the study showed that knowledge on disaster preparedness was mostly adequate (75.7%), policies on disaster preparedness were mostly very good (86.5%), emergency planning on disaster preparedness was very good (78.4%), warning system on disaster preparedness sufficient (75.7%) and resource mobilization regarding disaster preparedness is very good (78.4%). From this research, it can be concluded that the workers understand all aspects of emergency preparedness and response in an effort to deal with disaster risk. Conclusion: Based on the results of the study, the researcher provides suggestions for more frequent socialization of emergency response, updating the installation of disaster signs, increasing the number of means of transportation, updating the information system, providing location maps and evacuation routes as well as training for disaster preparedness teams